Weak-Form Review and Judicial Independence: A Comparative Perspective - Mirza Satria Buana (Constitutional Review, 2024)
This article examines the Court’s judicial review power that has gradually shifted from a strong-form review into a weak-form review. The shifting into weak-form review may affect judicial independence, both de facto or de jure, because Justices have considered the Legislature’s responds on the Court’s decisions. This approach diminishes the Court’s supremacy toward lawmakers. This article explores comparative insights from various countries that utilize those reviews, notably the United States of America (strong review), and commonwealth countries (weak review). It also elaborates on some ‘anomalies’ from both reviews. It raises two important questions: what insights can be learned from other countries’ judicial practices, particularly on the use of weak- form review? And, does weak-form review suitable to be enforced in Indonesia’s context? The weak review that is manifested in conditional decisions claims to be more politically palatable. Despite that strategic reason, the practice of conditional decision is prone to misuse as it could decrease constitutionalism and judicial independence. This paper argues that the weak-form review is not suitable for Indonesia’s constitutional law context, because the country lacks prerequisites and preconditions of strong control through parliament. The Indonesian Constitutional Court must return to its genuine authority as a strong-form review to strengthen legal constitutionalism.